2015
DOI: 10.1016/j.juro.2014.09.117
|View full text |Cite
|
Sign up to set email alerts
|

Lithotripter Outcomes in a Community Practice Setting: Comparison of an Electromagnetic and an Electrohydraulic Lithotripter

Abstract: Purpose We assessed patient outcomes using 2 widely different contemporary lithotripters. Materials and Methods We performed a consecutive case series study of 355 patients in a large private practice group using a Modulith® SLX electromagnetic lithotripter in 200 patients and a LithoGold LG-380 electrohydraulic lithotripter (TRT, Woodstock, Georgia) in 155. Patients were followed at approximately 2 weeks. All preoperative and postoperative films were reviewed blindly by a dedicated genitourinary radiologist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In literature there are many studies that compare different lithotripters. Some studies evaluate, as we did, the differences between electrohydraulic and electromagnetic lithotripters, however, the results are discordant (3,4). In our series electromagnetic lithotripter has better results.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In literature there are many studies that compare different lithotripters. Some studies evaluate, as we did, the differences between electrohydraulic and electromagnetic lithotripters, however, the results are discordant (3,4). In our series electromagnetic lithotripter has better results.…”
Section: Discussionmentioning
confidence: 53%
“…tially the same way (2). Many studies compare different lithotripters or different energy source in order to evaluate efficacy (3,4). In our institution, we used an electrohydraulic lithotripter and when it was no longer available, we used an electromagnetic one.…”
mentioning
confidence: 99%
“…While several studies have compared the efficacies of electrohydraulic and electromagnetic ESWT for treating ureter stones, the results obtained with the 2 types of generators were not significantly different [ 29 30 ]. However, we anticipate that electromagnetic ESWT will be found to have theoretical advantages that could be applicable in clinical practice in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several types of shock wave generation are available, including electrohydraulic, electromagnetic, and piezoelectric ( 13 ). It was reported that there was no significant difference in treatment outcomes between electromagnetic and electrohydraulic methods ( 14 ). According to the results from both clinical and experimental researches, the commended shockwave frequency for PU is 60/min (1 Hz) ( 15 ).…”
Section: Literature Searchmentioning
confidence: 99%